Study the Role of Eosinophilic Cationic Protein, Copper and Iron in Women Infected with Trichomonas vaginalis Parasite (Journal of Pharmaceutical Negative Results, 2022)
Since Trichomonas vaginalis (T. vaginalis) only manifests as a trophozoite stage during sex, it is typically transmitted during sex as a trophozoite. The purpose of this study was to determine the concentrations of copper, iron, and Eosinophil cationic protein (ECP) in vaginitis patients. Between July and November 2021, 355 suspected patients who visited the AL-Zahra maternity and pediatrics laboratory in the AL-Najaf region (Iraq) and 30 healthy respondents of the same age participated in the study. According to the manufacturer's instructions, the ELISA technique was used to measure the levels of three biomarkers in serum (copper, iron, and ECP). On the other hand, the colorimetric approach was used to measure the copper concentration. The investigation showed that in the blood sample of T. vaginalis-infected patients, the amounts of copper and iron considerably decreased (P > 0.05). In contrast, the serum levels of ECP considerably increased (P > 0.05) when compared to the control group. As a result of the T. vaginalis infection, copper levels in the blood are dramatically impacted, according to the current study's findings. The current study results suggested that the T. vaginalis infection alters serum iron and ECP concentrations, significantly affecting copper levels in the blood.